2013
DOI: 10.1097/bot.0b013e3182694a2d
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Nail Fixation of Fibular Fractures Associated With Tibial Shaft and Pilon Fractures

Abstract: Treatment of distal tibial fractures is technically challenging. The purpose of this study was to evaluate the use of distally locked retrograde Ender nail fixation of axially stable fibular fractures associated with these distal tibia fractures. During a 4-year span, we treated 23 fibular fractures, associated with either distal tibial metaphyseal or articular fractures, with a retrograde 3.5-mm Ender nail. The surgical protocol along with radiographic and clinical outcomes is presented. Using this technique,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…Asloum et al 15 reported a 100% rate of union in 36 patients treated with intramedullary nail fixation. A union rate of 100% was also found by Stewart et al 41 using a retrograde intramedullary nail. Intramedullary nail fixation of distal fibula fractures has been heavily discussed in the recent literature, largely with positive outcomes.…”
Section: Discussionsupporting
confidence: 59%
“…Asloum et al 15 reported a 100% rate of union in 36 patients treated with intramedullary nail fixation. A union rate of 100% was also found by Stewart et al 41 using a retrograde intramedullary nail. Intramedullary nail fixation of distal fibula fractures has been heavily discussed in the recent literature, largely with positive outcomes.…”
Section: Discussionsupporting
confidence: 59%
“…Bone is one of the tissues that can heal without fibrous scar formation and bone healing occurs by tissue regeneration [Marsell and Einhorn, ]. In an attempt to recover full function and restore the anatomy, several treatment methods have been employed for treatment of fracture, including intramedullary nail fixation, plate and screw fixation, and surgical fixation [Drobetz et al, ; Stewart et al, ; Baldwin et al, ]. However, these methods are associated with highly variable outcomes, especially in elderly populations.…”
mentioning
confidence: 99%
“…We fixed fibula in all cases either with plating or intramedullary rod. Christopher et al [16] reported that an intact fibula or fibular plate fixation provides initial rotational stability and minimizes varus or valgus angulation in distal tibia fractures treated with either nailing and plating group [16]. 65% were closed and 35% grade 1 open type in group 1 cases compared to 55% closed and 45% grade 1 open in group 2.…”
Section: Discussionmentioning
confidence: 99%